Evaluation of satisfaction level of Sehat Sahulat Programme among patients and doctors in Lahore and Gujranwala districts, Pakistan - Manzoor, Iram; Imran, Momal; Niaz, Areeha; Arshad, Aqsa; Mehmood Majoka, Ashir; Dawood, Ashar Bin (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the satisfaction level of patients and doctors with a health insurance scheme in two districts of Punjab province. Method: The analytical, cross-sectional study was conducted from June 2022 to November 2022 at Farooq Hospital West Wood Branch, Akhtar Saeed Trust Hospital, Lahore, Pakistan, and the District Headquarter Hospital, Gujranwala, Pakistan. The sample included doctors and adult inpatients receiving treatment under the Sehat Sahulat Programme. Data was collected using a pilot-tested, self-structured questionnaire. Data was analysed using SPSS 25. Results: Of the 565 subjects, 414(73%) were patients and 151(26%) were doctors. Among the 414 patients, 248(59.9%) were from Gujranwala and 166(40%) from Lahore. Overall, 401(97%) patients and 128(85.4%) doctors expressed satisfaction with the health insurance scheme. Quality of hospitals assigned, quality of curative services, quality and availability of medicines, service provision delayed due to the insurance scheme, having to bear additional expenses, lower financial burden, and overall quality of service were the factors that were significantly associated with the satisfaction level of the patients (p<0.05). Among the doctors, the overall satisfaction level was associated with the availability of medicine and the satisfaction with the payment procedure (p<0.05). Conclusion: Overall satisfaction rate among both doctors and patients with the Sehat Sahulat Programme was high. Key Words: Sehat sahulat card, Health insurance, National health policy.